2020
DOI: 10.1039/d0ma00554a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doping-induced local structure change in a Cr2Ge2Te6 inverse resistance phase-change material

Abstract: We investigated the crystallization behavior of Cr2Ge2Te6 (CrGT) and the effect of nitrogen (N) doping on it. We revealed that Ge or Cr-centered defective octahedral structure dominated in the amorphous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…© 2024 The Japan Society of Applied Physics corresponding to E g 2 and A g 1 modes, respectively. 34) As the annealing temperature increased, the Raman peaks became more pronounced, and other weak peaks, e.g., corresponding to E g 3 , E g 4 , and A g 2 modes, emerged. Based on the similarity to the Raman spectrum of single crystalline CrGT, we concluded that the annealing of CrGT thin films stimulated the growth of crystalline domains.…”
Section: Resultsmentioning
confidence: 97%
“…© 2024 The Japan Society of Applied Physics corresponding to E g 2 and A g 1 modes, respectively. 34) As the annealing temperature increased, the Raman peaks became more pronounced, and other weak peaks, e.g., corresponding to E g 3 , E g 4 , and A g 2 modes, emerged. Based on the similarity to the Raman spectrum of single crystalline CrGT, we concluded that the annealing of CrGT thin films stimulated the growth of crystalline domains.…”
Section: Resultsmentioning
confidence: 97%
“…Another example is the theoretical prediction of the 2D FE material family M 2 (Ge, Sn) 2 Y 6 . One of the recently discovered 2D ferromagnetic materials, Gr 2 Ge 2 Te 6 [89] , [90] , [91] , exhibits Ge atom interlayer flipping behavior under high-pressure [ 92 , 93 ] and during the amorphous Cr 2 Ge 2 Te 6 crystalline process [94] . This indicates the possibility of inducing ferroelectricity in Cr 2 Ge 2 Te 6 -like structures through Ge atom displacement.…”
Section: Strategy-ii: Design New 2d Fes By Designing New 2d Fe Struct...mentioning
confidence: 99%
“…Based on isothermal resistive change (Fig. 3c), the 10-year data retention temperature (T 10years ) was estimated to be 262 °C for the reset state, a value much higher than the T 10years for GST: 85-110°C 36,37 or other PCMs (T 10years of 173 -221 °C 20,[38][39][40] (Table S1)).…”
Section: Memory Device Propertiesmentioning
confidence: 99%